P46-T Unexpected electrophysiological findings in a boy with Balo concentric sclerosis. Issue 7 (July 2019) - Biedroń, Agnieszka; Gergont, Aleksandra; Kroczka, Sławomir
Abstract : Background: Balo concentric sclerosis is a rare form of multiple sclerosis (MS) characterized by tumefactive demyelination. Clinical presentation is usually polysymptomatic, however motor and sensory symptoms are the most common. Tetany is rarely found in patients with It can manifest by tingling and muscle cramps. Once suspected EMG tetany test should be performed. Material and Methods: A 15 year old boy with hand paresis, paresthesias and visual disturbances was admitted to the Chair of Pediatric and Adolescent Neurology Jagiellonian University Collegium Medicum in Cracow in August 2018. Results: Head MRI revealed concentric demyelination. Result of lumbar puncture was positive for oligoclonal bands. Infection agents were excluded. Additionally the boy suffered from recurrent syncopes. Video-EEG test did not reveal abnormalities. However during hyperventilation he experienced paresthesias in the right upper limb. During hospitalization paresthesias reappeared and were associated with involuntary finger flexion in right arm. EMG tetany test was performed giving strongly positive electrophysiological and clinical result. Electrolytes levels were within normal limits. PTH level was normal and vitamin D level low borderline. The boy was diagnosed with Balo concentric sclerosis and immunomodulating treatment has been introduced based on dimethyl fumarate. Six month observation has revealed good clinical outcome and treatment tolerance. Additionally vitamin D3 supplementation has been order. No signs of tetany has been observed since last hospitalization. Conclusions: We report an unexpected result of EMG tetany test in a boy with Balo concentric sclerosis, probably due to low borderline vitamin D3 concentration and additional emotional stress.